Fetal Intervention for Refractory Supraventricular Tachycardia Complicated by Hydrops Fetalis. (12th March 2022) - Munoz, Jessian L.; Lewis, Ariana L.; Song, Jun; Ramsey, Patrick S.
Abstract : Introduction . Few reports have shown promising treatments for refractory fetal tachycardia. Data are limited regarding optimal treatment, route of treatment, and medication dosages. Over 90% of cases of fetal tachycardia can be attributed to supraventricular tachycardia (SVT). The first-line treatment of fetal SVT is transplacental digoxin. Case Presentation . We present the management of a patient with fetal tachyarrhythmia diagnosed at 24 weeks and offer a unique approach for treatment. Fetal intramuscular injection of 72.3 mcg of digoxin allowed for resolution of SVT and sustained normal sinus rhythm. Further assessment in the third trimester showed persistent hydrops in the setting of mirror (Ballantyne's) syndrome resulting in delivery. Discussion/Conclusion . Our observations suggest that a one-time injection of digoxin allows for complete resolution of SVT. Utilizing an invasive approach for management of SVT that is resistant to traditional treatment modalities appears to both be therapeutic and decrease maternal adverse effects associated with more toxic effects of other transplacental medications.